1995
DOI: 10.1063/1.469968
|View full text |Cite
|
Sign up to set email alerts
|

The microwave spectrum and OH internal rotation dynamics of gauche-2,2,2-trifluoroethanol

Abstract: Articles you may be interested inStructure and tunneling dynamics in a model system of peptide co-solvents: Rotational spectroscopy of the 2,2,2trifluoroethanolwater complex A comparison of the properties of 2,2,2-trifluoroethanol and 2,2,2-trifluoroethanol/water mixtures using different force fieldsThe microwave spectra of CF 3 CH 2 OH and CF 3 CH 2 OD have been investigated from 5 to 26 GHz with a pulsed-nozzle Fourier-transform microwave spectrometer and from 26 to 42 GHz with an electric resonance optother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 25 publications
8
57
0
4
Order By: Relevance
“…The monomer oscillates between the two enantiomeric gauche forms with a 170 ps period, which is much slower than for ethanol [195] but orders of magnitude faster than MFE because the process is largely limited to hydrogen atom motion. Two different hydrogenbond topologies can be realized in the dimer.…”
Section: Methodsmentioning
confidence: 98%
“…The monomer oscillates between the two enantiomeric gauche forms with a 170 ps period, which is much slower than for ethanol [195] but orders of magnitude faster than MFE because the process is largely limited to hydrogen atom motion. Two different hydrogenbond topologies can be realized in the dimer.…”
Section: Methodsmentioning
confidence: 98%
“…The favored conformations of the fluoroethanols all have oxygen synclinal with a fluorine, again in conformity with experiment, with the O-H hydrogen directed toward a fluorine. [17][18][19] …”
Section: Computationalmentioning
confidence: 99%
“…The favored geometry of gaseous trifluoroethanol, for instance, brings the O-H group close to one of the fluorine atoms, with a hydrogen-fluorine distance of 2.56 Å. 9 The analogous structure does not seem realistic for a trifluoroethoxy group adsorbed on a surface. Imposition of appropriate conformational constraints on the gas-phase ethanols reveals a correlation between the ∆H rxn for gas-phase dehydrogenation and the ∆E act for -hydrogen elimination in ethoxy groups.…”
Section: Introductionmentioning
confidence: 99%
“…For comparison of the structural parameters obtained in this study for 2,2-difluoroethanol, we first tried the reported [20] values for gauche 2,2,2-trifluoroethanol but soon found that the assumed parameter for the C-C bond was much too short by at least 0.020 Å since it was transferred from the carbon-carbon distance for 1,1,1-trifluoroethane [21]. With the OH group placed on the other end of the CF 3 CH 3 molecule, the CC bond of trifluoroethanol is expected to be much longer.…”
Section: Discussionmentioning
confidence: 99%
“…[4]; calculated values from structural parameters in Table 4 c Experimental rotational constants Ref. [20]; calculated values from structural parameters in Table 9 Fig in frequency but with an A(55%)/C(40%) hybrid band and a predicted intensity of 28.3 km/mol. There appears to be one band at 489 cm -1 with either a B/C or A/C contour but the intensity is significantly larger than 8.4 km/mol as predicted for the Gg form so it is most reasonable to assign it as arising from both conformers although there is a relatively weak C-type band at 515 cm -1 , which could be m 17 for the Tg conformer.…”
Section: Conformational Stability and Barriers To Internal Rotationmentioning
confidence: 99%